Individual Exploration, Sensemaking, and Innovation: A Design for the Discovery of Novel Information1. Issue 6 (December 2013) - Jenkin, Tracy A.; Chan, Yolande E.; Skillicorn, David B.; Rogers, Keith W.
ABSTRACT Discovering novel information can result in the generation of potentially valuable new ideas and can therefore be beneficial to organizations interested in innovation. To be useful, novel information must have a particular relationship to existing organizational knowledge. It must be far enough away to qualify as novel, but it must be close enough that it can be understood and exploited. Therefore, a key challenge for novel‐information discovery (NID) is to find concepts that have such relationships to a given starting point or focal concept of interest. Despite the potential benefits, organizations face a number of challenges when discovering novel information on the Web: locating it, understanding its relevance, and making sense of it given the constraints and biases of existing mental models. In this article, we develop an understanding of the challenges of NID and how a tool can support individuals in locating and translating novel information into novel ideas. Using a design science approach, we develop a design theory for NID. A prototype is developed and evaluated. Our findings show that an NID tool performs better than other Web search tools such as Google in terms of the perceived levels of novel information provided and radicalness of the ideas generated.